From Friend of the Country to Helpful Citizen: an Approach to Patriotic Speech at the Royal Economic Society of Madrid under the Old Regime - Martín-Valdepeñas Yagüe, Elisa (Cuadernos de Historia Moderna, 2012)
The Royal Economic Society of Madrid, founded in 1775, was a leading propagandist for the achievements of the Enlightenment and attempted through its writings to encourage minorities open to reform to work together to promote public happiness. The society believed the entire community should be involved in this task, beginning with the King, whom they extolled for his interest in the economic and material progress of Spain. In their prolific writings, they repeatedly used words such as homeland, nation, patriotic, and even citizen, often with deliberate vagueness. These men portrayed themselves as patriots through their writings, since they felt they were working for the common good.